MÉTODO DELPHI EN ESTUDIOS DE PROSPECTIVA TECNOLÓGICA: Una aproximación para calcular el número de expertos y aplicación del coeficiente de competencia experta “K” - JHON WILDER ZARTHA SOSSA; JUAN MANUEL MONTES HINCAPIÉ; IVAN DARIO TORO JARAMILLO; RAUL HERNANDEZ ZARTA; HECTOR SAMUEL VILLADA CASTILLO; JOSE LUIS HOYOS CONCHA (Biotecnología en el Sector Agropecuario y Agroindustrial, 2017)
This paper deals with the Delphi method, its origins and characteristics. The main aspect to address is to provide information to identify an adequate number of experts in the choice of topics in the applications of the Delphi method in foresight. For that purpose, one Delphi study was evaluated in the period 2012 - 2015 on priority technologies regarding biodegradable packaging in the year 2032. On the results of this study, the incidence of the number of experts was evaluated with 9, 15, 22 and 24 experts. The results highlighted the existence of common core of technologies that were priorities from analysis 9 to 24 experts; regarding the expert competence coefficient "k" the results with the 16 experts with a coefficient "k" greater than or equal to 0.8, in four of the five groups, achieved high agreement percentages in relation to the core group of priority topics.